ANALISIS PEMETAAN EFEKTIVITAS IKLAN PRODUK PADA MEDIA ONLINE BANNER ADS DENGAN MENGGUNAKAN MODEL EPIC (Studi Kasus: Iklan Produk Advan di Portal Media Online) - Michael Christian (Business Management Journal, 2017)
The shift of advertising strategey changed the budget of promotion in any enterprises (product and/or services). Consumer behavior has come to the digital trens (internet) which caused the marketers think harder regards to delivering its own product an/or services to consumers. Printed media, broadcast media and the technology too the online media has been proven by these enterprises. The differences of promotion strategy in media can be seen at the creatitvity of information delivered by online banner ads. This study tends to find the effectivity of Advan ads at detik.com using the EPIC Model. All of the factors show a good position of ads by looking at maps.